2017
DOI: 10.1016/j.ajic.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Working with influenza-like illness: Presenteeism among US health care personnel during the 2014-2015 influenza season

Abstract: Background Health care personnel (HCP) working while experiencing influenza-like illness (ILI) contribute to influenza transmission in health care settings. Studies focused on certain HCP occupations or work settings have demonstrated that some HCP often continue to work while ill. Methods Using a national nonprobability Internet panel survey of 1,914 HCP during the 2014–2015 influenza season, we calculated the frequency of working with self-reported ILI (ie, fever and cough or sore throat) and examined reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 15 publications
4
123
1
3
Order By: Relevance
“…Presenteeism, defined as the practice of coming to work despite illness, in HCWs with ILI is a known concern. 25, 26 We found that 64% of the HCWs in our outbreak continued to work despite having ILI and based on timing of symptoms, we suspect this outbreak was related to, or at least accelerated by, high rates of presenteeism. The suspected index patient in this outbreak was an HCW.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Presenteeism, defined as the practice of coming to work despite illness, in HCWs with ILI is a known concern. 25, 26 We found that 64% of the HCWs in our outbreak continued to work despite having ILI and based on timing of symptoms, we suspect this outbreak was related to, or at least accelerated by, high rates of presenteeism. The suspected index patient in this outbreak was an HCW.…”
Section: Discussionmentioning
confidence: 68%
“…This further emphasizes a need for a culture change across the health care industry to limit the risk that ill HCWs pose to inpatients if, and when, they present for duty with an ILI. 26 Banach et al 27 describe the potential for patient visitors to contribute to nosocomial spread of influenza. Although the 2 family members who became infected in this outbreak did not cause the outbreak, this situation demonstrates the challenges in establishing practical visitation policies that limit the potential for visitors to contribute to nosocomial spread of ILI during influenza season.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys during previous influenza years reported that over 40% of HCWs might come to work while suffering from respiratory infections, increasing the risk of transmission to staff and to patients. 39 Even in settings of potential staff shortages, institutions must maintain policies to prevent HCWs with symptoms of the disease to avoid work and to seek appropriate medical care for themselves.…”
Section: "Staff": Increasing the Safety Of Trained Personnelmentioning
confidence: 99%
“…In a study undertaken in a children's hospital in Philadelphia, 299 (55%) of medical staff who were surveyed, reported that they would work with significant respiratory symptoms, despite acknowledging the infection risk to their co-workers and patients [31]. In another study over 40% of US HCWs who were surveyed worked with symptoms of influenza-like illness [32]. Whilst it is important to avoid presenteeism, it may be occasionally unavoidable e.g.…”
Section: Workforce Capability and Capacitymentioning
confidence: 99%